Entrepreneurial Orientation and Business Potential toward MSME Financial Performance through Managerial based Entrepreneur Finance during Digital Transformation - Intan Shaferi; Alisa Tri Nawarini; Cut Misni Mulasiwi (ICEETE Conference Series, 2026)
This study focus at how being entrepreneurial and having good business potential affect the financial performance of small businesses, for example micro, small, and medium enterprises. It also considers how the way managers handle business finance plays a role in this relationship, especially in the context of digital transformation. As digital tools keep changing how businesses work, small and medium-sized enterprises need to improve their business skills and better manage their money to keep their finances stable over time. A study that uses numbers and collects data through questionnaires to find out information. Data was gathered from 50 small and medium-sized business owners in Central Java, Indonesia, using a structured questionnaire. The respondents who took part were chosen through purposive sampling because they were actively running their businesses and involved in making financial decisions. The research model was studied using Partial Least Squares Structural Equation Modeling, a method that works well for research that is still exploring ideas and for studies with a smaller number of participants. The results show that having an entrepreneurial mindset and good business opportunities help improve how managers handle finance, which in turn makes the financial results of small and medium-sized businesses better. Moreover, the way managers handle money in an entrepreneurial setting partly explains how entrepreneurial attitude, the potential of the business, and its financial results are connected. This research adds value to the fields of entrepreneurship and small businesses by showing how financial decisions made by managers in a company help improve its financial results during the shift towards digital technologies.